Assessment of performance of bio self-healing mortar using diatomaceous earth and silica fume - AlBughdadi, Ahmed (AUC Knowledge Fountain, 2016)
Cracking represents a major threat for the integrity and performance of structures. There are many factors that initiate cracking that are related to environment, properties of concrete itself and several other variables that are difficult to control. Repairing becomes inevitable for concrete structures; however it could be costly and time consuming. Self-healing concept has been introduced to construction materials in order to enhance their performance and extend their service life with less repair. The objective of this study is to assess the performance of Portland cement mortar incorporating self-healing Bacillus Pseudofirmus bacteria using Diatomaceous earth (DE) to immobilize precursor and bacteria in mortar and lowering the pH level of mortar by using silica fume to provide a suitable growth environment for bacteria to generate limestone. The specimens were prepared at three different bacteria dosages and three DE dosages in addition to burned Bentonite dosages and w/c of 0.5. Cracking of specimens was induced by load percent concept after 3 days and tests were performed at 7, 14 and 28 days of curing. The testing scheme for the bacteria viability and mortar included sporulation tests, compression test, indirect tension test, rapid chloride permeability test, chemical soundness test and ultrasonic pulse velocity in addition to the effect of mixing techniques on strength. Results were compared against ordinary Portland cement mortar that includes 15% silica fume. Micro analysis of the healed crack surface of the different specimens was performed and a parametric study was conducted to select the optimum dosage of bacteria, DE and mix design combination as well. This work reveals that self-healing bacteria is promising technique in minimizing cracking and enhancing mortar physical and mechanical properties such as increasing compressive and tensile strength of mortar and decreasing permeability of mortar. The SEM Pictures shows that using bacteria enhances mortar through precipitating calcite in the voids and cracks of mortar. It is recommended to expand this work to cover more dosages of bacteria, different types of self-healing as well as concrete specimens.